Occupational stress and intention to leave among frontline health care professionals during covid-19 pandemic at Khamis Mushyt general hospital in Assir region, Saudi Arabia - Assiri, Aisha Ali Abdulla (Journal of medical and pharmaceutical sciences, 2022)
Aim: The study aimed to investigate the relation between occupational stress and intent to leave for the healthcare professionals at Khamis Mushyt Hospital during Covid-19 pandemic. Method: A quantitative method based on a cross-sectional study; the study employed a sectional research design. A total of (374) frontline health-care professionals were included in the study from all workers at Khamis Mushyt Hospital. The self-administered questionnaire was distributed using a convenience sample method in this study. The information gathered was entered into a special database. Results: The results showed that there is no relation between the stress that frontline healthcare workers have witnessed during the peak of Covid-19 pandemic and their intent to leave their jobs. However, there is a relation between some demographics and the level of stress the healthcare professional experienced. Recommendations: Based on the results I had; I recommend to reduce daily total working hours to prevent the occupational stress between the healthcare professional (medical / non-medical). I also recommend that other studies should to be carried out about stress factors like job satisfaction, work environment stress, and measure its impacts on the intent to leave. Extra studies need to be carried out for more investigation about stress factors. Conclusion: the majority of the participants have experienced different levels of occupational stress, the participants who responded that they will definitely leave is not critical and there is no correlation between Occupational stress and Intention to leave.